2018
DOI: 10.3390/molecules23061390
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Mercapto-(2-Oxoindolin-3-Ylidene)Acetonitriles from 3-(4-Chloro-5H-1,2,3-Dithiazol-5-Ylidene)Indolin-2-ones

Abstract: Alkylidene oxindoles are important functional moieties and building blocks in pharmaceutical and synthetic chemistry. Our interest in biologically active compounds focused our studies on the synthesis of novel oxindoles, bearing on the exocyclic double bond at the C8, CN, and S groups. Extending the potential applications of Appel’s salt, we developed a new synthetic approach by investigating the reactions of C5-substituted 2-oxindoles with 4,5-dichloro-1,2,3-dithiazolium chloride (Appel’s salt) to give origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…This procedure is a modified one-pot version of the method reported in the literature. 15 4-(2-Aminophenyl)-2-phenyl-4-oxobutyronitrile 18 ( 6aa ) (250 mg, 1.00 mmol), DMSO (0.8 mL), and KOH (224 mg) were mixed in a 25 mL round-bottom flask and stirred at room temperature for 30–40 min. Then, acetic acid (8.5 mL) and hydrazine hydrate (98%, 4 mL) were added and the reaction mixture was heated under reflux for 4 h. After this period, the solution was allowed to cool down and then poured down into 100 mL of crushed ice.…”
Section: Experimental Partmentioning
confidence: 99%
See 3 more Smart Citations
“…This procedure is a modified one-pot version of the method reported in the literature. 15 4-(2-Aminophenyl)-2-phenyl-4-oxobutyronitrile 18 ( 6aa ) (250 mg, 1.00 mmol), DMSO (0.8 mL), and KOH (224 mg) were mixed in a 25 mL round-bottom flask and stirred at room temperature for 30–40 min. Then, acetic acid (8.5 mL) and hydrazine hydrate (98%, 4 mL) were added and the reaction mixture was heated under reflux for 4 h. After this period, the solution was allowed to cool down and then poured down into 100 mL of crushed ice.…”
Section: Experimental Partmentioning
confidence: 99%
“…Additional purification can be achieved by recrystallization from EtOH of i -PrOH. The title compound was obtained as a white solid, mp 306.5–308.9 °C ( i -PrOH), lit 15 mp 308–310 °C, R f 0.34 (acetone). Yield 148 mg (0.57 mmol, 57%).…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we expanded this family of dithiazolylidenes to analogues of electron-rich pyridols, 16 and, in 2018, Thiéry et al reported the reaction of Appel salt 1 with indolin-2ones. 31 The absence of additional chemistry of dithiazolylidene 8 is surprising. Compound 8 has a deep-purple color, owing partly to its ortho-quinone methide structure, and to a strong contribution of a charge-separated resonance form.…”
Section: Letter Syn Lettmentioning
confidence: 99%